Probing the chemo-mechanical performance of cementitious materials - Constantinides, Georgios; Van Vliet, Krystyn J.; Smith, James F.; Ulm, Franz Josef (My University, 2008)
Recent advances in modeling [1] allow one to upscale the mechanical response of complex heterogeneous material systems (concrete being an example) and obtain effective properties that can be used in structural mechanics applications. Upscaling techniques may vary from analytical, namely theoretical micromechanics, to numerical, namely finite element solutions, utilizing in the process physicochemical models that analytically [2] or digitally [3] synthesize microstructures. Such approaches, which have their origin at the level of the individual chemical constituents of the composite material, provide a direct link between physical chemistry and mechanics [4]. Furthermore, they allow one to trace the origin of chemo-mechanical degradation at the length scale where the chemical reactions occur [5]. A common requirement to all modeling approaches is the need for intrinsic mechanical properties of the individual constituents composing the composite material, and their temporal response as chemical softening or stiffening occurs. In the case of concrete, the main constituent phase that governs the macroscopic response (Calcium Silicate Hydrates or in short C-S-H) manifests itself in the nm to μm length scale. This constituent phase cannot be recapitulated effectively ex-situ; one has to, therefore, access the mechanical properties of C-S-H in-situ at the length scale where it can be naturally found [6]. Refinements in instrumented nanoindentation allow one to efficiently determine the mechanical blueprint of these phases and trace their mechanical response in a temporal and spatial resolution [6, 7].
Keywords: Nanoindentation; Durability Performance; C-S-H; Calcium Leaching; Porcine skin